Biodegradation and Detoxification of Azo Dyes by Halophilic/Halotolerant Microflora Isolated From the Salt Fields of Tibet Autonomous Region China - Qiu, Hulin; Shen, Fengfei; Yin, Aiguo; Liu, Jiaxian; Wu, Biyu; Li, Ying; Xiao, Yunyi; Hai, Jinping; Xu, Bo (Frontiers in Microbiology, 2022)
This study aimed to decolorize azo dyes in high-salt industrial wastewater under high salt and low oxygen conditions using extreme halophilic/halotolerant bacteria screened from the salt fields of Tibet, which consisted of Enterococcus, unclassified Enterobacteriaceae, Staphylococcus, Bacillus, and Kosakonia. Under the optimal conditions, 600 mg/L Congo red, Direct Black G (DBG), amaranth, methyl red and methyl orange could be completely decolorized in 24, 8, 8, 12, and 12 hours, respectively. When the DBG concentration was 600 mg/L, NADH-DCIP, laccase, and azo reductase were confirmed to be the primary reductase and oxidase during the degradation process, and the degradation pathways were verified. The microflora could not only tolerate changes in salt concentrations of 0–80 g/L, but also displayed strong degradative ability. Under high salt concentrations (≥60 g/L NaCl), NADH-DCIP reductase was primarily used to decolorize the azo dye. However, under low salt concentrations (≤40 g/L NaCl), azo reductase began to function, and manganese peroxidase and lignin peroxidase could cooperate to participate in DBG degradation. Additionally, the halophilic/halophilic microflora was shown to convert the toxic DBG dye to metabolites of low toxicity based on phytotoxicity analysis, and a new mechanism for the microflora to degrade DBG was proposed based on intermediates identified by liquid chromatography-mass spectrometry (LC-MS). This study revealed that the halophilic/halophilic microflora has effective ecological and industrial value for treating wastewater from the textile industry.